1996
DOI: 10.1103/physreve.54.559
|View full text |Cite
|
Sign up to set email alerts
|

Extension and generalization of the Gay-Berne potential

Abstract: In this paper, we report a generalized form for the range parameter governing the pair interaction between soft ellipsoidal particles. For nonequivalent uniaxial particles, we extend the Berne-Pechukas Gaussian overlap formalism to obtain an explicit expression for this range parameter. We confirm that this result is identical to that given by an approach that is not widely recognized, based on an approximation to the Perram-Wertheim hard-ellipsoid contact function. We further illustrate the power of the latte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
209
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(212 citation statements)
references
References 26 publications
1
209
0
Order By: Relevance
“…Our model also comprises the anisotropic Gay-Berne potential, which can be seen as a generalization of the Lennard-Jones potential. Gay-Berne and Lennard-Jones models can be mixed through a generalized formalism, 58 as we have already done to describe headgroup-tail and water-tail interactions. Recent work in our group has provided further evidence of the validity of our multiscale approach; in that study, 116 water-octane partition coefficients for a range of solutes were calculated by Monte Carlo simulations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our model also comprises the anisotropic Gay-Berne potential, which can be seen as a generalization of the Lennard-Jones potential. Gay-Berne and Lennard-Jones models can be mixed through a generalized formalism, 58 as we have already done to describe headgroup-tail and water-tail interactions. Recent work in our group has provided further evidence of the validity of our multiscale approach; in that study, 116 water-octane partition coefficients for a range of solutes were calculated by Monte Carlo simulations.…”
Section: Discussionmentioning
confidence: 99%
“…58 Explicit formulas of potentials, forces, and torques for both the original Gay-Berne model and its generalized version are reported in detail elsewhere. 56,58,59 Intralipid bonds are modeled by the Hooke potential, as is standard practice. No angle or torsional potentials are present.…”
Section: Methodsmentioning
confidence: 99%
“…We start with the generalised expression for the shape parameter which governs the interaction between a pair of uniaxial, but non-identical, ellipsoidal gaussians [18]. This expression, which itself is an approximation to the hard ellipsoid contact function for non-identical ellipsoids [26], gives the contact distance between particles i and j of elongations l i , l j and breadths…”
Section: Computation Of the Contact Distancementioning
confidence: 99%
“…The first is a hard version of the truncated Stone expansion potential described in [1]. The second employs a novel approach, based on a parametric variant of the generalized Gay-Berne shape parameter [18], which yields an analytical expression for the contact distance between two pear-shaped objects.…”
Section: Introductionmentioning
confidence: 99%
“…In order to improve the accuracy of the coarsegrained calculations of non-bonded interactions, Golubkov and Ren [31] suggested that it should be better to take into consideration the anisotropic shape of the CG particle that can be characterized correctly by an anisotropic potential, Peijun Xu and Hujun Shen contributed equally to this work Electronic supplementary material The online version of this article (doi:10.1007/s00894-012-1562-5) contains supplementary material, which is available to authorized users. then the anisotropic Gay-Berne potential [32,33] is employed not only to describe the ellipsoid but also to represent the rigid bodies with other shapes, such as sphere and disk. In addition, electric multipole effects of the CG particle should be considered for the multipole expansion (including the charge, dipole moment and quadrupole moment) that gives the charge distribution more accurately than the fixed point charge for the CG particle.…”
Section: Introductionmentioning
confidence: 99%